THE BUSINESS JUDGEMENT RULES ( BJR ) DOCTRINE AS LEGAL PROTECTION AGAINST BOARD OF DIRECTORS IN BUMN - Aniek Tyaswati Wiji Lestari; Totok Tumangkar (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
This legal writing discusses the implementation of the Business Judgment Rules (BJR) doctrine, in relation to the legal protection of BUMN directors, where in carrying out management of BUMN, when the BUMN experiences losses the directors are deemed to have harmed state finances. In writing this law, it uses a type of normative legal research, with a statutory approach and a conceptual approach. The legal materials used are primary legal materials, namely Law Number 40 of 2007 concerning Limited Liability Companies and Law Number 19 of 2003 concerning BUMN. The research results show that Law Number 40 of 2007 concerning Limited Liability Companies basically regulates the protection of Directors in BUMN companies in protecting the rights of directors through the concept of the Business Judgment Rule doctrine as regulated in Article 97 Paragraph (5) and Article 104 Paragraph (4) Law Number 40 of 2007 concerning Limited Liability Companies. Through the Business Judgment Rule Doctrine, it has provided legal protection for directors of state-owned companies who cannot be held individually responsible for losses to state-owned companies by proving that the losses were not due to the fault or negligence of the directors of state -owned companies, have made business policies in accordance with good faith and the principle of prudence and the absence of personal conflicts of interest when making business policies by BUMN directors.